Interleukin-32γ in the Control of Acute Experimental Chagas Disease - Yarlla L. L. Braga; José R. C. Neto; Arthur W. F. Costa; Muriel V. T. Silva; Marcos V. Silva; Mara R. N. Celes; Milton A. P. Oliveira; Leo A. B. Joosten; Fátima Ribeiro-Dias; Rodrigo S. Gomes; Juliana R. Machado (Journal of Immunology Research)
Chagas disease (CD) is an important parasitic disease caused by Trypanosoma cruzi. Interleukin-32 (IL-32) plays an important role in inflammation and in the development of Th1/Th17 acquired immune responses. We evaluated the influence of IL-32γ on the immune response profile, pathogenesis of myocarditis in acute experimental CD, and control of the disease. For this, C57BL/6 wild-type (WT) and IL-32γTg mice were infected subcutaneously with 1,000 forms of Colombian strain of T. cruzi. In the histopathological analyzes, T. cruzi nests, myocarditis, and collagen were quantified in cardiac tissue. Cytokine productions (IL-32, IFN-γ, TNF-α, IL-10, and IL-17) were measured in cardiac homogenate by ELISA. The IL-32γTg mice showed a better control of parasitemia and T. cruzi nests in the heart than WT mice. Infected-WT and -IL-32γTg mice showed similar levels of IFN-γ, TNF-α, and IL-17, but IL-10 was significantly higher expressed in IL-32γTg than in WT mice. The cytokine profile found in IL-32γTg animals contributed to body weight maintenance, parasitemia control, and survival. Our results indicate that the presence of human IL-32γ in mice infected with the Colombian strain of T. cruzi is important for infection control during the acute phase of Chagas disease.